NARRATIVE REVIEW: STUDY OF MICROBIAL-BASED TIPPING POINTS AS HALAL FOOD PRODUCTS - Muhammad Faizal Fathurrohim (International Journal Mathla’ul Anwar of Halal Issues, 2022)
The majority of Indonesia's population is Muslim. Halal product testing needs to be tested for its tipping point, especially those made from microbes. Microbial products have been determined by the critical point procedure. The critical point of the idolatry of a food product is a stage of food production where a product allows it to become haram status. Identification of testing the critical point of a microbial product can go through several stages, namely food sources, microbial media, and processing procedures. Based on MUI, halal products are produced from animals or materials that are included in the halal category. The use of microbes in producing products is a rapid step in the food production process. Things that need to be considered in its processing include materials and growth media.